Groundwater Potential in The Confined Aquifer Cibeureum Formation Using the Jacob Method Pump Test, Bandung – Soreang Groundwater Basin, Bandung City, West Java Province - Priyono, Imam; Cahyaningtiyas, Martha Ayu (Journal of Geoscience, Engineering, Environment, and Technology, 2024)
High population growth increases demand for clean water. The greater the demand for clean water, the greater the extraction of groundwater. This large-scale extraction of groundwater is not balanced with the rate of groundwater recharge in aquifers, resulting in a decline in the water table. Groundwater subsidence is an ongoing problem in some areas of Indonesia, especially in densely populated areas. Bandung is one of the areas experiencing a decline in groundwater levels. The confined aquifer in the Cibeureum Formation of the Bandung-Soreang Groundwater Basin is one of the aquifers that is a source of clean water for the people of Bandung. Currently, the groundwater level in the aquifer continues to decline. The amount of potential groundwater discharge in this basin must be known, to limit the amount of groundwater withdrawal. This study aims to determine the amount of groundwater reserves, and ways to reduce the decline in groundwater levels in the basin. In this research, pumping test well data is used, which will be processed using the Jacob Method to obtain the value of groundwater reserves in the Bandung-Soreang Groundwater Basin. The amount of groundwater reserves in this basin is 67.50 L/sec. Meanwhile, the amount of groundwater is 43.87 L/sec.